UPAYA MENINGKATKAN KEMAMPUAN MENENTUKAN PELUANG SUATU KEJADIAN DENGAN MODEL PEMBELAJARAN KOOPERATIF SCRIPT PADA SISWA KELAS IX-IPA 3 SMA NEGERI 2 MADIUN TAHUN PELAJARAN 2010/2011 - Jarot Susiloyoga (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
Based on experience from year to year high school students generally have difficulty in understanding the material probability of occurrence. This is because the students are not pleased with the material opportunities as a result of the use of learning methods monotonous, merely presenting the material, less engaging students to motivate generate curiosity, students had not been discussed to find and solve the problem. Script cooperative learning model is a combination of lecture and group work. In cooperative learning students are encouraged to work together in groups, helping each other solve problems, respectful of opinions among friends in the group so that each student has a share in order to achieve the learning objectives. The purpose of this study was to determine whether the Model Cooperative Script can improve the ability of students and student activity in determining the probability of occurrence in class XI-IPA3 SMAN 2 Madiun in the academic year 2010 / 2011. The data will be collected in descriptive research is a description of the learning activities and this study used a qualitative approach to the type of research is classroom action research. The results showed that the level of mastery learning in classical experienced a significant increase of sklus I of 58.33% to 86.11% in the second cycle, so that the second cycle students in classical learning completeness has been reached. In addition, the obtained level of activity in the first cycle was 67.64% with a classification of good ratings, while on the second cycle increased significantly ie 80.84% ​​with a classification of excellent ratings. Thus we concluded that the learning model cooperatif Script can improve the ability of students and student activity in determining the probability of occurrence in class XI-IPA3 SMAN 2 Madiun in the academic year 2010/2011.Keywords: Cooperative Script, Capabilities, Activities, Opportunities A Genesis